DESKRIPSI STRATEGI GURU KELAS MENANAMKAN NILAI PENDIDIKAN KARAKTER SISWA KELAS IV A - Yoga Valentino; Hery Kresnadi; Kartono Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to describe the strategy of classroom teachers to instill the value of character education in students in the classroom. The type of research is descriptive qualitative research with casestudy method. The subject of the study was the fourth grade A teacher at 39 Pontianak City Elementary School. Data collection techniques are interviews, observation and documentation. The results of the study show that teachers have implemented character education strategies, namely: 1) applying learning motivation that involves student participation; 2) create a conducive learning environment; 3) build supportive and caring relationships in the classroom and throughout the school; 4) positive behavior as role models for students; 5) creating opportunities for students and meaningful including in school life and in the classroom; 6) teach essential social and emotional skills; 7) create meaningful and relevant learning assignments; 8) no child is neglected, all students can realize their potential. Barriers to the implementation of the strategy of grade IV A teachers instilling the value of character education include internal and external factors. Internal factors arestill the lack of self-awareness of the students themselves to follow the strategies that the teacher gives and the teacher's lack of understanding about the theory of character planting. External factors, namely the environment and conditions, namely the pandemic that occurred